Evaluation of an electricity-free, culture-based approach for detecting typhoidal Salmonella bacteremia during enteric fever in a high burden, resource-limited setting. - Jason R Andrews; Krishna G Prajapati; Elizabeth Eypper; Poojan Shrestha; Mila Shakya; Kamal R Pathak; Niva Joshi; Priyanka Tiwari; Manisha Risal; Samir Koirala; Abhilasha Karkey; Sabina Dongol; et al. (Public Library of Science (PLoS), 2013)
In many rural areas at risk for enteric fever, there are few data on Salmonella enterica serotypes Typhi (S. Typhi) and Paratyphi (S. Paratyphi) incidence, due to limited laboratory capacity for microbiologic culture. Here, we describe an approach that permits recovery of the causative agents of enteric fever in such settings. This approach involves the use of an electricity-free incubator based upon use of phase-change materials. We compared this against conventional blood culture for detection of typhoidal Salmonella.Three hundred and four patients with undifferentiated fever attending the outpatient and emergency departments of a public hospital in the Kathmandu Valley of Nepal were recruited. Conventional blood culture was compared against an electricity-free culture approach. Blood from 66 (21.7%) patients tested positive for a Gram-negative bacterium by at least one of the two methods. Sixty-five (21.4%) patients tested blood culture positive for S. Typhi (30; 9.9%) or S. Paratyphi A (35; 11.5%). From the 65 individuals with culture-confirmed enteric fever, 55 (84.6%) were identified by the conventional blood culture and 60 (92.3%) were identified by the experimental method. Median time-to-positivity was 2 days for both procedures. The experimental approach was falsely positive due to probable skin contaminants in 2 of 239 individuals (0.8%). The percentages of positive and negative agreement for diagnosis of enteric fever were 90.9% (95% CI: 80.0%-97.0%) and 96.0% (92.7%-98.1%), respectively. After initial incubation, Salmonella isolates could be readily recovered from blood culture bottles maintained at room temperature for six months.A simple culture approach based upon a phase-change incubator can be used to isolate agents of enteric fever. This approach could be used as a surveillance tool to assess incidence and drug resistance of the etiologic agents of enteric fever in settings without reliable local access to electricity or local diagnostic microbiology laboratories.